2013
DOI: 10.1111/and.12072
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cinnamon (Cinnamomum zeylanicum) bark oil in the prevention of carbon tetrachloride-induced damages on the male reproductive system

Abstract: In this study, it was aimed to investigate the likelihood of detrimental effects of carbon tetrachloride (CCl4 ) on male reproductive system through oxidative stress mechanism and also protective effects of cinnamon bark oil (CBO). For this purpose, 28 healthy male Wistar rats were divided into four groups, seven rats in each. Group 1 received only olive oil daily; group 2 was treated with 100 mg kg(-1) CBO daily; group 3 was treated with only 0.25 ml kg(-1) CCl4 weekly; and group 4 received weekly CCl4 + dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
3
28
1
1
Order By: Relevance
“…Excessive generation of free radicals-induced DNA damage results in increased testicular apoptotic germ cell (Maheshwari et al, 2009). It has been reported that long-term CCl 4 administration causes testicular DNA damage (Khan, 2012;Yüce et al, 2013). The apoptotic cell index of CCl 4 group was found to be significantly higher than the control group in the present study.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Excessive generation of free radicals-induced DNA damage results in increased testicular apoptotic germ cell (Maheshwari et al, 2009). It has been reported that long-term CCl 4 administration causes testicular DNA damage (Khan, 2012;Yüce et al, 2013). The apoptotic cell index of CCl 4 group was found to be significantly higher than the control group in the present study.…”
Section: Discussioncontrasting
confidence: 43%
“…Therefore, disturbances in the synthesis of androgens and proteins can cause negative changes in body weight and especially in the reproductive organ weights (Fernandes et al, 2007). It has been reported that CCl 4 administration results in reduced body and testis weights (Castilla-Cortazar et al, 2004;Manjrekar et al, 2008;Khan and Ahmed, 2009;Yüce et al, 2013) and decreased testosterone level (Khan, 2012;Khan and Ahmed, 2009). In the present study, CCl 4 caused significant decreases in body weight and also weights of testes, epididymides, and accessory sex glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as the testis, prostate (Jiang et al ., ), epididymis (Hudson et al ., ) and germ cells (Liu et al ., ) contain CYP isozymes, it is possible that CCl 4 causes oxidative damage in lipids of these tissues and cells (Abraham et al ., ). Acute or chronic CCl 4 administration has been reported to cause morphological, structural and functional damages in reproductive system through oxidative toxicity in male laboratory animals (Kalla & Bansal, ; Horn et al ., ; Manjrekar et al ., ; Khan & Ahmed, ; Abdou et al ., ; Khan, ; Yüce et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…CBO is an antioxidant and may have a protective effect through an oxidative stresss mechanism on the male reproductive system (Yüce et al, 2014). CINA is a major constituent of CBO (~70%) which is an active antifungal compound (Singh et al, 1995) that can inhibit NF-kB through signal tansduction pathways NIK/IKK, ERK, and p38 MAPK, thereby showing good antioxidant properties (Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%